COMPARATIVE STUDY ON THE ROLE AND EFFICACY OF COUMARIN DERIVATIVES AND OCREOTIDE IN THE REDUCTION OF SEROMA IN POST OP MODIFIED RADICAL MASTECTOMY PATIENTS (CAHIERS MAGELLANES-NS, 2024)
OBJECTIVES: Breast cancer, with an annual incidence of 2.1 million new cases, is one of the most prevalent carcinomas worldwide. Breast cancer treatment entails the use of surgery, radiotherapy as well as chemotherapy. However while treating for breast cancer, complications are an inevitable occurrence of which post operative seroma is an issue for all patients and practitioners. Hence the key objective of this study aims to investigate, compare and determine any significant differences in seroma formation following the administration of octreotide and coumarin derivatives in postoperative Modified Radical Mastectomy (MRM) patients.METHODS: This single-center cross-sectional study was conducted in the Department of General Surgery at Saveetha Medical College Hospital. 50 breast carcinoma patients who met the study criteria and underwent MRM from June 2023 to June 2024 were taken up for the study. After detailed history, examination and necessary investigations, these patients were divided into two groups of 25, each receiving one of the study drugs. Parameters analyzed included age, diagnosis, drug adverse reactions, discharge day, drain collection volume and drain duration.RESULTS: The study demonstrates that elderly patients were the most common group involved. The study findings indicate that both Tablet Lympedim and Injection Octreotide are effective in managing postoperative conditions in breast carcinoma patients. However, Tablet Lympedim was associated with earlier drain removal and discharge, suggesting a potential advantage in terms of recovery time. The safety profiles of both drugs were similar, with no significant difference in the rate of adverse reactions.